The trend of wearing contact lenses now-a-days Coolense: A famous contact lenses brand - Abanty, Rifat Tashfiha (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.